Comparison of pre-competitive anxiety between futsal players of sub-16 and sub-19 category - Ferreira, Sergio Costa (2021)
The aim of the study was to compare the values of anxiety in futsal players from different age categories. Materials and methods. The sample consisted of 18 male futsal players which 9 of them are from the under-16 category (mean=16 years) and 9 from the under-19 category (mean=18.22 ±0.22 years). The Competitive State Anxiety Inventory-2 (CSAI-2) questionnaire was used, which was applied 30 minutes before the games. Results and Discussion. In individual values, in the sub-16 category, 100% of the players expressed Self-confidence higher than the values of Cognitive Anxiety and Somatic Anxiety and 66.66% of the players had Cognitive Anxiety less than Somatic Anxiety. In the under-19, individual data showed that 88.88% of the players had higher self-confidence than the values of Cognitive Anxiety and Somatic Anxiety. Also 77.77% of the players expressed lower Cognitive Anxiety values than Somatic Anxiety. In relation to the averages, the players in the sub-16 and under-19 categories presented in Low Cognitive Anxiety, Medium Somatic Anxiety and High Self-confidence. The under-16 and under-19 showed similarity in Cognitive Anxiety. In the under-19, Somatic Anxiety was superior to the under-16 and greater Self-confidence in the under-16. In both categories, the anxiety values had the same classification. Conclusion. In terms of average values, anxiety between the categories were different, however, the classification of anxiety was the same.